CONVENTIONAL EDUCATIONAL WITH INDOOR & OUTDOOR MODULES ON DISASTER PREPAREDNESS IN HIGH SCHOOL STUDENTS IN TOMOHON - Rolly Harvie Stevan Rondonuwu; Monica Tandiayuk; Dorce Sisfiani Sarimin (Media Kesehatan Politeknik Kesehatan Makassar, 2019)
Indonesia is one of the countries that experiences quite a lot of natural disasters such as floods, landslides, earthquakes, volcanic eruptions, tsunamis. Increased volcanic volcanic activity in Indonesia's volcanoes allows for potential eruptions in several regions. Disasters that occur in the community require good handling based on targeted disaster management, given that disasters come unexpectedly, for that many things must be prepared carefully including educational interventions on disaster management. This study aims to determine the differences using conventional indoor modules and modules indoor & outdoor on volcanic disaster preparedness in high school students in the city of Tomohon, North Sulawesi.The research design in this study was Quasi experiment one group pre-post-test. In this design high school students were given a pretest before being given education to find out the initial condition, and posttest after being given education, then it would be known whether there was a difference between the scores pretest and posttest . The population in this study were all Lokon high school students, and the sample was 10th grade students totaling 60 people, held in September 2016.The results showed that the experimental group student learning outcomes were better than the control group. The average posttest value of the experimental group students (73.27) was higher than the mean value of the control group posttest (66.17). thus there are differences in scores in the group given the indoor module intervention with the indoor-outdoor module intervention group with a value of p 0.001. (t independent test)Based on the results of the study concluded that there are differences in knowledge between students who are taught using the method indoor learning with students who use methods indoor & outdoor learning. Suggestion: expected teaching methods indoor + outdoor can be developed as a variety of learning methods Keywords: conventional Education, indoor & outdoor modules, Disaster